Pengabdian Masyarakat: Pelatihan Kader Tentang Inhalasi Sederhana Aromaterapi Daun Mint Dalam Penurunan Sesak Napas Dirumah - Afrieani Deasy; Isvana; Ririn; Ayu (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Shortness of breath is a common symptom associated with various respiratory disorders and can be managed through complem entary therapies, one of which is simple inhalation using peppermint (Mentha piperita) aromatherapy. However, the knowledge of commu nity health volunteers regarding this technique remains limited. This community service program aimed to improve the knowledge of health volunteers about simple inhalation as a non-pharmacological approach to help relieve shortness of breath at home. The activity was conducted on June 7, 2026, in RW 06, Babakan Sari Block, Batujajar Barat Village, West Bandung Regency, involving 10 health volunteers selected through total sampling. The training consisted of lectures, discussions, demonstrations, hands-on practice, and pre-test and post-test evaluations. The results demonstrated a significant improvement in participants' knowledge, with the proportion of volunteers in the good knowledge category increasing from 20% to 70%, while no participants remained in the poor category after the training. Statistical analysis revealed a significant difference (p = 0.02). Furthermore, all participants were able to perform the simple inhalation technique according to the prescribed procedure. The training was effective in enhancing the knowledge and practical skills of health volunteers in providing community health education.